Effect of small boat engine noise on hearing loss of fishermen and efficiency of small boat engine silencer - S. Sinworn; N. Viriyawattana (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The fishery workers are affected by the noise produced by motorboats, which is caused by long-term (more than 7 hours per day), exposure to high frequencies and hazardous noise levels. The detrimental impact of the loud noise emitted by small boat engines affects the hearing abilities of fishermen in Thailand has been well-documented. In light of this, the primary aim of the present study was to assess the potential hazards associated with noise exposure and develop an effective silencer that can effectively mitigate the noise generated by fishing boats. The study was conducted in Songkhla Lake, located in Thailand, providing a suitable setting for the current study.METHODS: During an 8-hour work period, 300 sample fishers were monitored using sound-level and noise-dose meters. Their response to noise was evaluated through an audiometry test and a questionnaire. Furthermore, a silencer was engineered to decrease the noise emissions from boat engines. Utilizing the solid work technique, the exhaust silencer was designed based on a model of the internal exhaust pressure. The sound level at the end of the exhaust silencer pipe was determined by employing a sound meter and recording it at a speed of 4,000 revolutions per minute. The designed silencer was installed on the exhaust pipe of the boat engine to align with the current operation of the engine. The objective was to measure the variation in noise levels before and after the installation of the silencer. The sound level meter of type I, equipped with a weighted circuit incorporating an A network (weight A), closely resembles the auditory response of the human ear to sound. Prior to assessing the noise produced by the engine, it was ensured that the engine had been running for a minimum of 5 minutes. The sound level of the small boat's engine was then measured using a type I sound-level meter positioned at a 45-degree angle behind the engine, and at a distance of 0.5 meter.FINDINGS: The results indicated that evaluating the risks associated with being exposed to high levels of noise from boat engines had an impact on the auditory capacity of fishermen. The right ear was more severely damaged than the left at frequencies of 6,000 (23 people) and 8,000 (20 people) Hertz at sound levels of 85 decibels A and above. This data is valuable for the development of a silencer aimed at mitigating sound pressure levels that impact the loudness of sound across different frequency levels, considering a boat engine's maximum acceleration of 4,000 revolutions per minute through the application of solid design principles. Subsequently, the silencer will be tested on Thai fishermen who are regularly exposed to noise, demonstrating a reduction in engine noise of over 23 decibels A within the frequency range of 100 to 10,000 Hertz.CONCLUSION: The auditory abilities of fishermen are adversely impacted by the intensity and high pitch of the noise emitted by small boat engines. The solid design technique is employed to create a silencer for a boat engine with a maximum acceleration of 4000 revolutions per minute, operating at frequency levels of 2000, 3,000, 4,000, 6,000, and 8,000 Hertz. Exposure to loud noise can pose a significant risk to the hearing health of fishermen. However, their safety can be ensured by implementing effective measures to reduce the loudness by more than 23-42 decibel A. By employing such work practices, the noise levels experienced by fishermen can be kept below the hazardous threshold of > 85 decibels A.